THE EFFECT OF ELECTRONIC WORD OF MOUTH (E-WOM) ON PURCHASE INTEREST THROUGH EMINA'S BRAND IMAGE - Eka Irma Alfiyanti Aridla; Ratna Handayani; Dhita Dhora Damayanti (Sean Institute, 2022)
This research aims to find out whether Electronic Word of Mouth and Brand Image are expected to partially influence Emina's cosmetic Purchase Intention , in addition, direct or indirect influence between Electronic word of Mouth and Purchase Intention or between Electronic word of mouth with buying interest through brand image can also be known . This research involves several people who live in Lamongan who act as users of Emina products both as consumers and potential consumers. A total of 100 respondents will be used as samples in this research . The tools used are; (1) validity test; (2) reliability test; (3) multiple regression analysis test; (4) t test; ( 5 ) f test; (6) determination test; (7) path analysis . Based on the results of the analysis using SPSS 20. It can be concluded from the results of the Electronic Word of Mouth t-test on purchase intention of 8.031 > t-table 1.6604 so that it can be said that e-wom can partially influence buying interest in Emina cosmetics . The test on the e-wom variable (X 1 ) on brand image (Y 2 ) is 10.677 > t-table 1.6604 so that it can be said that e-wom simultaneously influences the image of Emina's cosmetic brand. Tests on e-wom variables (X 1 ) and brand image (Y 2 ) on buying interest (Y 1 ). of 6.898 > t-table 1.6606 So it is said that the e-wom variable through the brand image variable influences the variable of interest in buying Emina cosmetics partially . And for testing path analysis, namely the direct effect between e-wom and buying interest 0.630 but for the indirect effect as much as 0.132 .